Neurodegeneration-associated mitochondrial proteins, CHCHD2 and CHCHD10–what distinguishes the two? - Ikeda, Aya; Imai, Yuzuru; Hattori, Nobutaka (Frontiers in Cell and Developmental Biology, 2022)
Coiled-coil-helix-coiled-coil-helix domain containing 2 (CHCHD2) and Coiled-coil-helix-coiled-coil-helix domain containing 10 (CHCHD10) are mitochondrial proteins that are thought to be genes which duplicated during evolution and are the causative genes for Parkinson’s disease and amyotrophic lateral sclerosis/frontotemporal lobe dementia, respectively. CHCHD2 forms a heterodimer with CHCHD10 and a homodimer with itself, both of which work together within the mitochondria. Various pathogenic and disease-risk variants have been identified; however, how these mutations cause neurodegeneration in specific diseases remains a mystery. This review focuses on important new findings published since 2019 and discusses avenues to solve this mystery.